2001
DOI: 10.1590/s1516-14392001000300008
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of silica by sol-gel method using formamide

Abstract: In this work we obtained microporous and mesoporous silica gels by sol-gel processing. Tetraethylortosilicate (TEOS) was used as precursor. Nitric acid and hydrofluoric acid were used as catalysts. In order to study the affect of formamide as drying additive, we used a molar ratio alkoxide/formamide of 1/1. The performance of formamide in obtaining crack-free gels was evaluated through monolithicity measurements. The structural evolution occurring in the interconnected network of the gels during thermal treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
66
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(76 citation statements)
references
References 21 publications
6
66
0
4
Order By: Relevance
“…Furthermore, a diagnostic Si-O-Si asymmetric stretching vibration is centred on 1132 cm −1 [31,32] and the absorption signal at 920 cm −1 is assigned to the stretching vibration of silanol groups on the surface of the amorphous solid [33].…”
Section: Ftirmentioning
confidence: 99%
“…Furthermore, a diagnostic Si-O-Si asymmetric stretching vibration is centred on 1132 cm −1 [31,32] and the absorption signal at 920 cm −1 is assigned to the stretching vibration of silanol groups on the surface of the amorphous solid [33].…”
Section: Ftirmentioning
confidence: 99%
“…Lenza et al reported the spectral shift to higher frequency of Si-O band due to thermal treatment on the sol-gel derived silica, and ascribed it to a larger intratetrahedral bond angle, a stronger Si-O bond strength, and a shorter bond length. 24 Though the exact origin of the spectral shift of Si-O band observed in the present system is not clear at present, such explanation can be applicable to the present system.…”
mentioning
confidence: 58%
“…The absorption bands around 3,450 and 1,635 cm -1 are usually attributed to symmetrical and asymmetrical O-H stretching vibrations, and respectively to the bending of H-O-H from water molecules adsorbed on sample surface. The broad absorption bands recorded between 1,070 and 1,130 cm -1 , as well as the shoulder at 1,215 cm -1 are ascribed to Si-O-Si asymmetric stretching vibration [43]. The weak absorption band recoded at 800 cm -1 is assigned to symmetric stretching vibration of Si-O-Si bonds in amorphous silica, while the 467 cm -1 absorption band is associated with Si-O-Si bond bending vibration [43].…”
Section: Resultsmentioning
confidence: 93%